In vitro organogenesis of Abutilon indicum (L.) Sweet from leaf derived callus and assessment of genetic fidelity using ISSR markers. Issue 1 (2nd January 2019) - Seth, Sen; Panigrahi, Jogeswar
ABSTRACT: This study reports on in vitro regeneration of Abutilon indicum plantlets through callus mediated organogenesis. The leaf explants implanted on Murashige and Skoogs (MS) medium supplemented with 4.52 µM 2, 4-Dicholorophenoxy acetic acid (2, 4-D) and 8.88 µM 6 Benzyladenine (BA) showed highest response (70.3%) for callus proliferation, but these callus did not showed any morphogenetic differentiation on the same medium even after 12 weeks. Whereas, subsequent sub-culture of this green proliferated callus on MS medium added with 2.68µM α-Napthalene acetic acid (NAA), 8.88µM BA and 543 µM Adenine sulphate showed the highest frequency (62.2%) of multiple shoot-buds production and also elongation of shoots. Well developed shoots were efficiently rooted in vitro on half strength MS medium supplemented with 7.38 µM Indole-3-butyric acid (IBA). Seventy per cent of in vitro regenerated plantlets were successfully established in garden and were morphologically alike to the donor plants. The genetic homogeneity of these in vitro regenerated plantlets was also affirmed by inter simple sequence repeat (ISSR) analysis using eight ISSR primers. This standardised in vitro organogenesis protocol supplements a good platform for the conservation of A. indicum germplasms and also caters for the needs of the herbal industry.